1993
DOI: 10.1104/pp.103.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Tolerance in Wheat (Triticum aestivum L.) (I. Uptake and Distribution of Aluminum in Root Apices)

Abstract: We investigated the uptake and distribution of AI in root apices of near-isogenic wheat (Triticum aesfivum L.) lines differing in AI tolerance at a single locus (Altl: aluminum tolerance). Seedlings were grown in nutrient solution that contained 100 p~ AI, and the roots were subsequently stained with hematoxylin, a compound that binds AI in vitro to form a colored complex. Root apices of Alsensitive genotypes stained after short exposures to AI (10 min and 1 h), whereas apices of AI-tolerant seedlings showed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
3
12

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(188 citation statements)
references
References 16 publications
8
165
3
12
Order By: Relevance
“…Third, we have demonstrated that the accumulation of A1 in the apices of AI-tolerant roots was significantly less than in AI-sensitive genotypes (Table 111). This agrees with previous studies by Polle et al (1978), Tice et al (1992), Rincón and Gonzales (1992), and Delhaize et al (1993a), but in the present study we included severa1 improvements. First, we used near-isogenic lines of wheat, which allowed us to be confident that any differences observed between the tolerant and sensitive genotypes were related to the Alfl locus, which confers AI tolerance in these lines (Delhaize et al, 1993a).…”
Section: Two-factorsupporting
confidence: 93%
See 2 more Smart Citations
“…Third, we have demonstrated that the accumulation of A1 in the apices of AI-tolerant roots was significantly less than in AI-sensitive genotypes (Table 111). This agrees with previous studies by Polle et al (1978), Tice et al (1992), Rincón and Gonzales (1992), and Delhaize et al (1993a), but in the present study we included severa1 improvements. First, we used near-isogenic lines of wheat, which allowed us to be confident that any differences observed between the tolerant and sensitive genotypes were related to the Alfl locus, which confers AI tolerance in these lines (Delhaize et al, 1993a).…”
Section: Two-factorsupporting
confidence: 93%
“…This agrees with previous studies by Polle et al (1978), Tice et al (1992), Rincón and Gonzales (1992), and Delhaize et al (1993a), but in the present study we included severa1 improvements. First, we used near-isogenic lines of wheat, which allowed us to be confident that any differences observed between the tolerant and sensitive genotypes were related to the Alfl locus, which confers AI tolerance in these lines (Delhaize et al, 1993a). Second, we chose concentrations of AI that were at least 20-fold lower than those used previously and that inhibited growth in the Al-sensitive genotype but not the Al-tolerant genotype.…”
Section: Two-factorsupporting
confidence: 93%
See 1 more Smart Citation
“…Differential staining of root apices with hematoxylin preceded detectable differences in total AI concentrations found in the root apices of wheat (Triticum aestivum) plants differing in Al tolerance (Delhaize et at., 1993). It is, therefore, presently not possible to account for, with any certainty, the differences observed in the staining intensity of plant roots treated with Al and stained in hematoxylin.…”
Section: Discussionmentioning
confidence: 99%
“…Rincón & Gonzalez (1992) observed that the level of sensitivity to Al was correlated with its concentration in the meristems, suggesting that the metabolic exclusion in the meristems was an important mechanism of tolerance. Delhaize et al (1993) investigated the function of the organic acids and observed that the presence of Al in the nutrient solution stimulated the secretion of malic acid. These authors also found that the final 3 to 5 mm of the roots formed a primary source of the secreted organic acid; thus, there was a correlation between tolerance and high secretion of root exudates.…”
Section: Resultsmentioning
confidence: 99%